Frontiers in Complex Dynamics 2014
DOI: 10.1515/9781400851317-012
|View full text |Cite
|
Sign up to set email alerts
|

Unmating of rational maps: Sufficient criteria and examples

Abstract: Abstract. Douady and Hubbard introduced the operation of mating of polynomials. This identifies two filled Julia sets and the dynamics on them via external rays. In many cases one obtains a rational map. Here the opposite question is tackled. Namely we ask when a given (postcritically finite) rational map f arises as a mating. A sufficient condition when this is possible is given. If this condition is satisfied, we present a simple explicit algorithm to unmate the rational map. This means we decompose f into p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 14 publications
0
22
0
1
Order By: Relevance
“…On the other hand, regarding the question whether a rational map arises as a mating of polynomials, we have the following result obtained in [8], see also [7] and [9]. Theorem 4.19 (Meyer).…”
Section: Existence Of Matingsmentioning
confidence: 87%
“…On the other hand, regarding the question whether a rational map arises as a mating of polynomials, we have the following result obtained in [8], see also [7] and [9]. Theorem 4.19 (Meyer).…”
Section: Existence Of Matingsmentioning
confidence: 87%
“…Theorem 2.4 expresses when a mating can be viewed as equivalent to a rational map-but what about when a rational map can be viewed as a mating? In [9], it is shown that a postcritically finite rational map with Julia set the 2-sphere can be expressed as a mating if the map possesses a pseudo-equator :…”
Section: 3mentioning
confidence: 99%
“…Unmating of rational maps. In [9], Meyer comments that the existence of a pseudo equator is sufficient but not necessary to be indicative of a mating. The methods of this paper work in the quadratic cases that a pseudo equator can in some manner be found.…”
Section: 2mentioning
confidence: 99%
“…Another way to produce examples of Thurston maps is by mating two postcritically finite polynomials of the same degree, yielding a Thurston map of equal degree [19,20].…”
Section: Thurston's Theoremmentioning
confidence: 99%